The effect of motivational interviewing training on dentistry students of Tehran University of Medical Sciences on oral health index of patients referring to periodontix section - Neda Moslemi; Rayka Jamali (Babol University of Medical Sciences, 2016)
ABSTRACT BACKGROUND AND OBJECTIVE: Motivational interviewing (MI) has recently come to interest in the field of oral hygiene. It is a non-defense technique that aims at facilitation of attitude change. The purpose of this study was to define the effect of MI training on dental students of Tehran University of Medical Sciences (TUMS) on oral health index of referring patients. METHODS: This study was performed on12 dental students in periodontics department in TUMS. First a workshop was carried out for oral health education. Then the method of MI training by role play model was conducted in a complementary workshop. The students were divided in 3 groups. The first student played the role of patient and the second played the role of dentist, and the third one played the role of referee. The students were asked to role play the scenarios of 3 different patients. After the completion of MI training program, they trained their patients with regard to oral hygiene according to MI or conventional method. O'Leary plaque index of referred patients were registered at baseline, 2 weeks, and 2 months after intervention by students to define the effect of MI training or conventional method on patients' oral health index. FINDINGS: The plaque index changes from baseline to two weeks after training in MI group (51.33±9.79) was significantly different from control group (29.33±11.75) (Pvalue=0.006). Also the plaque index changes from baseline to two months after training in MI group (49.16±9.92) was significantly different from control group (22.50±7.09) (Pvalue<0.001). CONCLUSION: Application of MI resulted in more improvement of oral health indices, adherent to follow up visits, and sustained effect of treatment comparing with the conventional training. Considering the inappropriate oral hygiene in periodontal patients (that is an important cause of periodontitis) training of oral hygiene to dental students via this method might decrease the incidence of periodontal disease and medical expenses.